Compatibility of two isolates of Beauveria bassiana Vuill. with insecticides used for the Hypothenemus hampei (Ferrari) control - RIVERA-MALO, ARMANDO; BUSTILLO-PARDEY, ALEX E.; MARÍN-MARÍN, PATRICIA (Revista Colombiana de Entomología, 1994)
Two Beauveria bassiana isolates and eight insecticide formulations were examined in vitro to determine compatible combinations for the Hypothenemus hampei management. Differences were found among the isolates. In addition, the isolates reacted in a different way depending on the insecticide formulation. Diazinon WP, malathion, and fenitrothion were the most toxic; the other insecticides had variable effects on the isolates. The inhibition effect increased throughout the mixing time. A fungistatic effect of the insecticides on the isolates was observed. The interaction in the spray tank could be avoided by using separate applications of the two products. However, this will represent a higher cost in the borer suppression.